Effect of a physiotherapy program in women with primary dysmenorrhea. (November 2015) - Ortiz, Mario I.; Cortés-Márquez, Sandra Kristal; Romero-Quezada, Luis C.; Murguía-Cánovas, Gabriela; Jaramillo-Díaz, Alfonso P.
Abstract: Objective: To evaluate the efficacy of a physiotherapy program for relieving symptoms of primary dysmenorrhea among Mexican women. Study design: This was a single-center, prospective, experimental, parallel group, randomized controlled trial. This cross-sectional study was performed at the Universidad Politécnica de Pachuca, Hidalgo, Mexico. Female patients with primary dysmenorrhea, age of 18–22 years; pain intensity from 4 to 10 cm on a Visual Analogue Scale (VAS); and sedentary lifestyle were included. The patients were then randomized to receive a physiotherapy program for three months or to no intervention program. The physiotherapy program consisted of overall stretching, specific stretches, Kegel exercises, jogging, and relaxation exercises. Patient evaluations of symptomatology and pain intensity were recorded basally and throughout for three menstrual periods. The data were entered into a computerized database for descriptive and inferential statistical analyses. Results: A per-protocol population of eighty three women with a mean age of 20.2 ± 1.8 years underwent the physiotherapy program, and seventy seven participants with a mean age of 20.4 ± 1.2 years received no treatment. The participant assessments of pain on the VAS during the second and the third menstrual cycles demonstrated a significant reduction in the treatment group ( p  < 0.05) compared with the control group. Conclusions: The results showed that strengthening, stretching and muscle relaxation techniques, in addition to jogging, are effective for reducing dysmenorrheic symptoms when they are regularly performed.